2015
DOI: 10.3390/ijms161226121
|View full text |Cite
|
Sign up to set email alerts
|

gga-miR-101-3p Plays a Key Role in Mycoplasma gallisepticum (HS Strain) Infection of Chicken

Abstract: Mycoplasma gallisepticum (MG), one of the most pathogenic Mycoplasma, has caused tremendous economic loss in the poultry industry. Recently, increasing evidence has suggested that micro ribonucleic acids (miRNAs) are involved in microbial pathogenesis. However, little is known about potential roles of miRNAs in MG infection of chicken. In the present study, using miRNA Solexa sequencing we have found that gga-miR-101-3p was up-regulated in the lungs of MG-infected chicken embryos. Moreover, gga-miR-101-3p regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…A previous study from our group showed that gga-miR-101-3p played an important role in MG infection (Chen et al, 2015). miR-101 regulates activation of MAPKs in macrophages to defend against microbial infection (Zhu et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…A previous study from our group showed that gga-miR-101-3p played an important role in MG infection (Chen et al, 2015). miR-101 regulates activation of MAPKs in macrophages to defend against microbial infection (Zhu et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…A large amount of evidence has demonstrated that miRNAs are involved in cellular behaviors with the aim of resisting or promoting inflammation during infections and inflammation in mammals [ 36 , 37 ]. Recently, we also reported the effects of gga-miR-19a, gga-miR-99a, and gga-miR-101-3p in MG-mediated inflammation in chicken [ 24 , 25 , 38 ]. However, the role of miRNAs in the MG-induced respiratory inflammation is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Other miRNAs, including miR-16 and miR-29a, are reported to participate in the protumoral inflammatory process by activating the TLR8 response on immune cells [ 15 ]. Recently, we also reported the role of gga-miR-101 and gga-miR-19a in regulating MG-HS infection and MG-HS-mediated inflammatory cytokine production in both DF-1 cells and the lungs of chicken embryos [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…GO, KEGG, miRNA-GO-network, path-net, and gene-net analyses determined that the altered miRNAs regulated a large number of genes that function throughout various signaling pathways including the MAPK pathway, the focal adhesion regulatory pathways, the Wnt pathway, and the JAK/STAT pathway (Zhao et al, 2017b). gga-miR-101-3p was found to be up-regulated in the lungs of MG-infected chicken embryos, and gga-miR-101-3p could target and inhibit the host EZH2 (enhancer of zeste homolog 2), a growth suppressor gene involved in the regulation of cell cycle progression and proliferation, to suppress the proliferation of chicken embryonic fibroblasts by blocking the G1-to-S phase transition (Chen et al, 2015). Additionally, SMARCA5 (SWI/SNF related, matrix associated, actin dependent regulator of chromatin, subfamily A, member 5) is a member of the SWI/SNF family that exhibits ATPase and helicase activities.…”
Section: Mirna Involved In Avian Mycoplasmosismentioning
confidence: 99%